(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
The article analyzes important reforms in the fields of education and healthcare in Uzbekistan since the years of independence, such as the study of foreign experience, the widespread teaching of foreign languages, and the strengthening of the material and technical base of educational institutions. The impact of equipping schools, vocational colleges, and technical educational institutions in Navoi, Bukhara, and Samarkand regions, providing them with educational materials, textbooks, computer classes, and international cooperation projects is studied. It is emphasized that these measures have served to improve the quality of education, ensure that students receive education in accordance with international standards, and train qualified personnel in the healthcare system.